Let's Pretend' children and joint action - Tollepsen, Deborah (2005)
According to many, joint intentional action must be understood in terms of joint intentions. Most accounts of joint intention appeal to a set of sophisticated individual intentional states. The author argues that standard accounts of joint intention exclude the possibility of joint action in young children because they presuppose that the participants have a robust theory of mind, something young children lack. But young children do engage in joint action. The author offers a revision of Michael Bratman's analysis of joint intention that reflects the socio-cognitive abilities young children do have. This revision makes sense of joint action among young children and equally well explains simple joint actions involving adults. - Reproduced.
Keywords: Children; Youth